Prevalence of Lifestyle Changes in Online Learning Technology among College Students During Covid-19 Pandemic - Vishnu, Priya; Prathap, Suganthirababu; Vinodhkumar, Ramalingam; Vignesh, Srinivasan; Kumaresan, Abathsagayam; Jagatheesan, Alagesan (INTI International University, 2023)
Background: Several students' academic careers were affected by the COVID 19 pandemic over the world, and it even caused a considerable disruption to the education industry, which intensified psychological distress. Objective: To estimate the prevalence of lifestyle changes happened in online learning by use of the Euro Quality of life 5D 5L questionnaire among college students during covid 19 pandemic. Methodology: About 670 college students were included. A pre-structured questionnaire was used to collect information. Based upon the selection criteria, the participants were selected for the study. Participants were asked to fill the Euro quality of life 5D 5L questionnaire. The evaluator was assigned to score each question. A demographic pre structured questionnaire containing details of personal data and impacts on quality of life was collected. Result: Mobility, self-care, regular activities, anxiety/depression and pain/discomfort are all heavily influenced, according to the statistical research. Results indicated that the overall health of the students were affected as the reported negative health (77.98%) was higher than the positive health (22.01%). Conclusion: In this study, students taking college level professional courses in online during covid 19 pandemic have seen a high prevalence of effect in their physical, emotional welling and decreased in overall health have been explored.